2016
DOI: 10.1186/s12870-016-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic comparison between two Vitis vinifera L. varieties (Trincadeira and Touriga Nacional) in abiotic stress conditions

Abstract: Background: Predicted climate changes announce an increase of extreme environmental conditions including drought and excessive heat and light in classical viticultural regions. Thus, understanding how grapevine responds to these conditions and how different genotypes can adapt, is crucial for informed decisions on accurate viticultural actions. Global transcriptome analyses are useful for this purpose as the response to these abiotic stresses involves the interplay of complex and diverse cascades of physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 81 publications
(115 reference statements)
2
49
0
Order By: Relevance
“…Thus, there is a pressing need to understand the existing genetic diversity between and within varieties, and its influence on the physiological potential of the available genotypes to respond to climate changes and foster new terroirs. In light of this, an assembly of 65 differentially expressed genes (DEGs), known to respond to abiotic stresses in two well‐studied genotypes, ‘Touriga Nacional’ and ‘Trincadeira’ (Rocheta et al ), was designed to scan gene expression in leaves of 10 traditional Portuguese varieties growing in two Portuguese regions with distinct environmental conditions: one with a typical Mediterranean climate and the other with a marked Atlantic influence (Carvalho et al ). Due to the experimental set‐up behind the array design, the genotypes were characterized as ‘sensitive’ or ‘tolerant’ to abiotic stress and, furthermore, the DEGs were able to distinguish the main abiotic stress that each genotype/environment was subjected and responding to (drought, heat or excess light; Carvalho et al ).…”
Section: Abiotic Stress In the Field: Learning To Adjust To Climate Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is a pressing need to understand the existing genetic diversity between and within varieties, and its influence on the physiological potential of the available genotypes to respond to climate changes and foster new terroirs. In light of this, an assembly of 65 differentially expressed genes (DEGs), known to respond to abiotic stresses in two well‐studied genotypes, ‘Touriga Nacional’ and ‘Trincadeira’ (Rocheta et al ), was designed to scan gene expression in leaves of 10 traditional Portuguese varieties growing in two Portuguese regions with distinct environmental conditions: one with a typical Mediterranean climate and the other with a marked Atlantic influence (Carvalho et al ). Due to the experimental set‐up behind the array design, the genotypes were characterized as ‘sensitive’ or ‘tolerant’ to abiotic stress and, furthermore, the DEGs were able to distinguish the main abiotic stress that each genotype/environment was subjected and responding to (drought, heat or excess light; Carvalho et al ).…”
Section: Abiotic Stress In the Field: Learning To Adjust To Climate Cmentioning
confidence: 99%
“…(e.g. Tattersall et al , Xiao et al , Liu et al , Rocheta et al , Carvalho et al ). The HSP20 family is known for a strong upregulation in response to abiotic stresses (Swindell et al ), so the high expression levels of HSP20 found by Liu et al () in leaves of ‘Cabernet Sauvignon’ and of HSP17.9 found by Carvalho et al () in leaves of ‘Touriga Nacional’ upon HS were in line with findings from other species.…”
Section: Controlled Conditions: Uncovering Stress Synergies and Antagmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the potential roles of the 35 identified grapevine genes in ABA and drought stress, two different grapevine-related databases for ABA (Pilati et al , 2017) and drought (Rocheta et al , 2016) stress treatments were analyzed. RNA-seq analysis was performed of grapevine berry skins with or without ABA treatment for 20 h and 44 h. A GrapeGene GeneChips ® data analysis was performed of leaves from two Vitis vinifera L. varieties (Trincadeira, TR and Touriga Nacional, TN) grown under control and drought greenhouse conditions, as well as fully irrigated and non-irrigated field conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The heat maps were constructed using HemI software (Deng et al , 2014). To identify the predicted grapevine genes, two grapevine-related ABA (Pilati et al , 2017) and drought stress (Rocheta et al , 2016) databases were downloaded from the National Center for Biotechnology Information (NCBI) under BioProject accession number PRJNA369777 and the Gene Expression Omnibus (GEO) database under the number GSE57669.…”
Section: Methodsmentioning
confidence: 99%